2009
DOI: 10.1089/ten.tea.2008.0149
|View full text |Cite
|
Sign up to set email alerts
|

Minced Skin for Tissue Engineering of Epithelialized Subcutaneous Tunnels

Abstract: We used minced, autologous skin for neoepithelialization of surgically created subcutaneous tunnels in a large animal model. Partial-thickness skin grafts were harvested from the back region of five 50-60 kg Yorkshire pigs. The skin was minced to 0.8 x 0.8 x 0.3 mm particles. Silicone-latex tubes were covered with fibrin, rolled in minced skin, and placed in subcutaneous tunnels created in the abdominal area. For comparison, single cell suspensions of keratinocytes and fibroblasts in fibrin or fibrin only were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Fossum et al 14,15 have simplified the approach by mincing autologous skin epithelium or bladder mucosa for tissue transplants based on the method introduced by Meek. 13 They showed that the transplanted minced tissue remains viable, proliferates, and reorganizes on tubular latex scaffolds that serve as 3D molds and are later removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fossum et al 14,15 have simplified the approach by mincing autologous skin epithelium or bladder mucosa for tissue transplants based on the method introduced by Meek. 13 They showed that the transplanted minced tissue remains viable, proliferates, and reorganizes on tubular latex scaffolds that serve as 3D molds and are later removed.…”
Section: Discussionmentioning
confidence: 99%
“…13 Fossum et al have successfully used minced autologous skin for tissue engineering of epithelialized subcutaneous tunnels and have shown that the patient's body can be considered an in vivo incubator for the expansion of minced autologous skin or urothelium. 14,15 Hence, the use of minced tissue of bladder mucosa may serve as an alternative to in vitro culturing of urothelial cells. In the present study, we developed a scaffold suitable for rapid and direct combination with minced tissue and examined the in vitro culturing of a minced bladder mucosal tissue-scaffold hybrid.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Urothelium has also been shown to regenerate from the wound edges in a way similar to that of epithelium. [22][23] However, regeneration of the bladder wall tissue beneath the urothelium has been less well described. In vitro expansion of smooth muscle cells is made possible by using explant techniques , suggesting that migration to the edge of a wound before proliferation is a possible mode of action, and that the development might be through cell signaling.…”
Section: Urotheliummentioning
confidence: 99%
“…The collagen promotes ingrowth of granulation tissue, re-modelling and maturation of extra-cellular matrix 15 . As collagen is degraded, neovascularization and granulation tissue supports the transplanted minced particles that reorganize, migrate and expand [5][6][7]11,16 . Besides, collagen is a major natural component of the extracellular matrix both in skin and in the bladder and has been used for creation of scaffolds both in vitro and in vivo including wound healing studies and reconstructions in the urogenital system 17,18 .…”
Section: Discussionmentioning
confidence: 99%